Effect of Patient's Personality on Satisfaction with Their Present Complete Denture and after Increasing the Occlusal Vertical Dimension: A Study of Edentulous Egyptian Patients. (8th July 2014) - Fouda, Shaimaa M.; Al-Attar, Mohamed S.; Virtanen, Jorma I.; Raustia, Aune
Abstract : Complete denture wearers often find it difficult to accept a new denture. Personality traits are among the factors that possibly affect patient satisfaction with a complete denture. Our aim was to investigate the influence of patients' personality on satisfaction with their present denture and after an increase in the occlusal vertical dimension (OVD). Sixty edentulous patients with complete dentures (22 men and 38 women, mean age 66 years, and range 50–75 years) participated in the study. The age of their complete dentures ranged from 5 to 16 years. Patients' personalities were evaluated using the Arabic version of the Eysenck Personality Questionnaire. Their satisfaction with their dentures before and after restoration of the OVD and relining of the mandibular denture was evaluated using two questionnaires (I and II), Patients with a high score of neuroticism were less satisfied with their original dentures and after relining and an increase of OVD compared with patients with an average score in that trait. The personality trait of psychoticism was significant to patients' acceptance of an increase in OVD; that is, patients with a high score were less satisfied with their dentures after increase of OVD than patients with an average score. It is concluded that personality traits affect patients' acceptance of their complete dentures.